On a certain subclass of analytic univalent function defined by using Komatu integral operator - RAHROVI, Samira (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
In this paper a certain class of analytic univalent functions in the open unit disk is defined. Some interesting results including inclusion relations argument properties and the eect of the certain integral operator to the elements of this class are investigated. Mathematics Subject Classification (2010): 30C45.